PD‐1+CXCR5‐CD4+ T cells are correlated with the severity of lung adenocarcinoma malignant processes. (17th November 2021) - Wang, Jin; Tang, Yawei; Wu, Chunli; Li, Weiping; Wang, Bing; Jin, Minli; Yin, Chunlai; Li, Xia
Abstract: Peripheral helper T cells (Tph), characterized by PD‐1 + CXCR5 ‐ CD4 + phenotypes cells, played critical roles in inflamed tissues. Yet, to date, no researches were developed for lung adenocarcinoma (LADC) that was associated with worse outcome, advanced invasion and chronic inflammation in lung cancer cases. Accordingly, we aimed to investigate the impact of Tph cell subsets on the disease progress in peripheral blood and tumour tissue of patients with LADC. The percentages of Tph cell subsets in peripheral blood and tumour tissues obtained from 35 LADC and 10 healthy controls were examined by flow cytometry. In addition, invasion and tumour node metastasis (TNM) stage were also determined by Spearman's correlation test to assess their association with Tph cell subset. Furthermore, the effects of tumour microenvironment on Tph were investigated. The present results revealed that the percentage of Tph cells significantly increased in PBMC compared with healthy controls. In addition, similar results were observed in tumour tissues of LADC patients when compared to tumour‐adjacent control tissue. In addition, Tph cells were highly activated, appearing as ICOS increased, and associated with LADC invasion, compared with healthy controls. Notably, tumour environment could prefer Tph cells to promote tumour malignancy. Tph cells were observed in PBMC and tumour tissues from patients with LADC and highly associated with LADC invasion. Altogether, the present study indicates that elevated Tph cells could primarily be used as a potential therapeutic target in LADC patients.